Projectiles of Chaos: Symbolic (Dis)-Order in the Works of Yeats, Walcott and Adonis - Bassil, Tarek (Trinity College Dublin. School of English. Discipline of English, 2024)
This thesis proposes that there arises in postcolonial societies a species of literature that neither conforms to the dictates of a “stable” symbolic order nor is it determined by “symbolic history.” What is divulged in this type of literature is the influence of “chaos” – a force that attempts to upend the normative assumptions, machinations and influence of a given social order, or disclose a language that strives to go beyond what “symbols” determine of culture, the human psyche and the unconscious. My assessment takes in consideration the works of Adonis, Derek Walcott and W. B. Yeats – poets who belong to disparate regions of the globe and who had written at a time when their countries were in a state of political, cultural and social upheaval. The symbolic order in this thesis is defined in mostly Lacanian terms, and the methodology used is elaborated upon in conjunction with specific literature, postcolonial theory and criticism related to the three authors. In this manner, I argue that the sway of chaos on the signifiers of the symbolic order shepherds a para- symbolic impulse in postcolonial literature that has multiple ramifications. This impulse engenders within the psyche a paradoxical movement that attempts to unsuccessfully delineate chaos even as it ventures to use it to upend, invent and reinvent the social and cultural assumptions of a given region or age. Although the symbolic order is elucidated in mostly Lacanian terms, the conception of chaos uses a broad array of critics. Some of the works and notions which pertain to chaos and which I employ include Antonio Benítez-Rojo’s ideas in The Repeating Island, entropy as the second law of thermodynamics, chaos theory and fractal geometry as introduced by James Gleick and Edward Lorenz, the iii irreconcilability (hence, chaos) of myth in the works of Lévi-Strauss and Yeats’s A Vision, as well as the transforming impulse in Adonis’s theoretical work The Immutable and the Transforming. Other theorists that I use include, but are not limited to, Homi Bhabha, Julia Kristeva, Frederic Jameson, Gautam Basu Thakur, Mikhail Bakhtin, Slavoj Žižek, Walter Benjamin and Frantz Fanon. What this dissertation aims to disclose in the assessed works of the chosen writers is both a “desire” to push against the limits of symbols and what they determine of history, and an encounter with chaos where signifiers fail, where their very failure provides the conditions necessary for a brand-new poetics and literature to be produced and reproduced. Fundamentally, what I reveal is that although Yeats, Walcott and Adonis often employ different strategies in their poetry, beneath those strategies it is chaos that stitches all of their motives together as it weaves and tightens its thread across the different parts of the postcolonial globe.
APPROVED
Keywords: Derek Walcott; Adonis; Postcolonialism; Lacan; Symbolic Order; W. B. Yeats; Seminar on the "Purloined Letter"; Psychoanalysis; Chaos; Violence; Ireland; Caribbean; Syria; Lebanon; Myth; National allegory; Fanon; Bhabha; Zizek; Benitez-Rojo; Time; A Vision